(untitled) (REMUNOM, 2025)
Dietary habits exert a decisive influence on the modulation of the gut microbiota, directly impacting metabolic health and the development of chronic non-communicable diseases (NCDs). This study aimed to analyze, through a literature review, the influence of different dietary patterns on the composition and functionality of the gut microbiota and its effects on the pathophysiology of NCDs. Studies that investigated the interaction between varied diets and the gut microbiota, considering metabolic and immunological mechanisms, were selected. The evidence indicates that diets rich in fiber, prebiotics, polyphenols, and plant-based foods promote intestinal eubiosis, increase microbial diversity, and stimulate the production of short-chain fatty acids, such as butyrate. Conversely, dietary patterns characterized by the consumption of ultra-processed foods and saturated fats favor dysbiosis, low-grade chronic inflammation, and a higher metabolic risk. It is concluded that the adoption of balanced dietary habits constitutes an effective strategy in the prevention of NCDs, reaffirming the role of nutrition as an essential non-pharmacological tool for health promotion. Keywords: Gut microbiota; Nutrition; Non-communicable chronic diseases; Dysbiosis; Preventive nutrition